A Perspektif Tafsir Al-Qurthubi Tentang Krisis Akhlak Di Era Digital - Wildanul Af, Muhammad; Fadhli, Khairul; Saad, Muhammad (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2025)
The background of this study focuses on the moral crisis emerging due to shifting interaction patterns in the digital era. This crisis has intensified with the rise of social media, influencing ethical values and behavior. The research problem centers on how Tafsir Al-Qurthubi can provide ethical solutions for this issue. The study aims to explore Al-Qurthubi’s perspective on morality and its relevance to the digital age. The research employs a qualitative method with textual analysis through literature studies. Data sources include relevant Quranic verses, Tafsir Al-Qurthubi, and secondary references. The findings reveal that Al-Qurthubi offers moral solutions through principles such as taqwa (piety), careful speech, and ethical conduct. In conclusion, Tafsir Al-Qurthubi remains relevant in addressing ethical challenges in the digital era, particularly in guiding healthy social media interactions. The use of technology in moral education is also recommended as an additional solution.